2011
DOI: 10.1101/gr.125666.111
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific retargeting of an oncogenic transcription factor chimera results in dysregulation of chromatin and transcription

Abstract: Chromosomal translocations involving transcription factor genes have been identified in an increasingly wide range of cancers. Some translocations can create a protein “chimera” that is composed of parts from different proteins. How such chimeras cause cancer, and why they cause cancer in some cell types but not others, is not understood. One such chimera is EWS–FLI, the most frequently occurring translocation in Ewing Sarcoma, a malignant bone and soft tissue tumor of children and young adults. Using EWS–FLI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
124
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 67 publications
4
124
0
Order By: Relevance
“…To test whether FAIRE-enriched regions were likely to harbor regulatory elements, we annotated the sites from each cluster with active and repressive histone modifications. We also tested for association with targeting of numerous transcription factors, including those known to be important in endothelial cell biology, as assessed by ChIP-seq (17,19). (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test whether FAIRE-enriched regions were likely to harbor regulatory elements, we annotated the sites from each cluster with active and repressive histone modifications. We also tested for association with targeting of numerous transcription factors, including those known to be important in endothelial cell biology, as assessed by ChIP-seq (17,19). (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then adapted HT-FAIRE for high-throughput automation and applied it in a targeted screen. The screen was based on two regions selected from a set of Ewing sarcoma-specific sites that we had previously shown were accessible in multiple Ewing sarcoma cell lines with accessibility that was dependent on continued expression of EWSR1-FLI1 (17). Regions that consistently demonstrate FAIRE enrichment or lack of enrichment across many cell types were included as controls (see Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comparing binding of epitope-tagged EWSR1/FLI1 in an ES cell line (EWSR1502) to FLI1, Patel et al (2012) recently suggested that EWSR1/FLI1 directs chromatin remodeling at a proportion of distant sites. Interestingly, in our study, the predominant transcriptional behavior of genes associated with EWSR1/FLI1 without si- multaneous E2F3 binding was found to be repression.…”
Section: E2f/ets Regulatory Module In Ets-driven Cancersmentioning
confidence: 99%
“…• ENCODE dataset 2,3 • Lymphoblastoid cell lines (GM12878, GM12891, GM12892, GM18507, GM19239) • Ewing sarcoma (EWS502) 11 • Normal breast cells (patient-derived) 12 • Renal cell carcinoma (786-O) and breast cancer cells (MCF-7) 13 • Leukemia (patient-derived, TLX + T-ALL) 14 • Colon adenocarcinoma (LoVo) 15 • Prostate cancer (VCaP, LNCaP) 16,17 • Embryonic stem cells (pre-and post-embryoid body cells derived from H9-hESCs) 18 • Lung adenocarcinoma (A549) 19 • Chronic myelogenous leukemia (K562) 20 • Primary lung fibroblasts, astrocytes, and dermal fibroblasts 21…”
mentioning
confidence: 99%